Calpain-2 participates in the process of calpain-1 inactivation. Issue 11 (3rd November 2020) - Shinkai-Ouchi, Fumiko; Shindo, Mayumi; Doi, Naoko; Hata, Shoji; Ono, Yasuko
Abstract: Calpain-1 and calpain-2 are highly structurally similar isoforms of calpain. The calpains, a family of intracellular cysteine proteases, cleave their substrates at specific sites, thus modifying their properties such as function or activity. These isoforms have long been considered to function in a redundant or complementary manner, as they are both ubiquitously expressed and activated in a Ca 2+ - dependent manner. However, studies using isoform-specific knockout and knockdown strategies revealed that each calpain species carries out specific functions in vivo . To understand the mechanisms that differentiate calpain-1 and calpain-2, we focused on the efficiency and longevity of each calpain species after activation. Using an in vitro proteolysis assay of troponin T in combination with mass spectrometry, we revealed distinctive aspects of each isoform. Proteolysis mediated by calpain-1 was more sustained, lasting as long as several hours, whereas proteolysis mediated by calpain-2 was quickly blunted. Calpain-1 and calpain-2 also differed from each other in their patterns of autolysis. Calpain-2–specific autolysis sites in its PC1 domain are not cleaved by calpain-1, but calpain-2 cuts calpain-1 at the corresponding position. Moreover, at least in vitro, calpain-1 and calpain-2 do not perform substrate proteolysis in a synergistic manner. On the contrary, calpain-1 activity is suppressed in the presence of calpain-2, possibly because it is cleaved by the latter protein. These results suggest that calpain-2 functions as a down-regulation of calpain-1, a mechanism that may be applicable to other calpain species as well.